Discurso constelar e contingência: a pregnância de Mallarmé - Martha-Toneto, Diana Junkes Bueno [UNESP] (My University, 2011)
The aim of this article is to discuss Mallarmé‘s poem A throw of dice, establishing some theoretical interfaces among Jakobson‘s reading, Lacan‘s psychoanalysis and some elements from the French discourse analysis. The poem, considered a milestone of modern poetry, has already engendered various discourses about itself, what allows us to consider it here a permanent invention, or yet, a throw of dice in eternal whirl. Attentive to the roaring of such discourses, and available for listening the theory that contributes to the poem‘s critical analysis, the reading herein engaged bets on the profit that the Mallarmé‘s poem study carries, for the perception of contemporary poetry, which inherited from him the double-sided lyrical coin: high revision of the possibilities of invention and very strong metalanguage.

O objetivo deste artigo é discutir o poema ―Um lance de dados‖, de Mallarmé, por meio do estabelecimento de convergências teóricas entre a leitura jakobsoniana, a psicanálise lacaniana e alguns elementos da análise do discurso de linha francesa. O poema, considerado marco da poesia na modernidade, já engendrou inúmeros discursos a seu respeito, o que nos autoriza a considerá-lo aqui como invenção permanente ou, ainda, como um lance de dados em eterno turbilhonar. Atenta aos ruídos desses discursos e disponível à escuta teórica que contribui para a análise crítica do poema, a leitura aqui empreendida aposta nos ganhos que a leitura do poema de Mallarmé tem para a percepção do estado das artes da poesia contemporânea, que dele herdou a dupla face da moeda lírica: a alta revisão das possibilidades de invenção e a excessiva metalinguagem.
Constellate discourse and contingency: Mallarmé’s contemporary permanence
Keywords: Mallarmé; Um lance de dados; contingência; psicanálise; discurso; Mallarmé; A throw of dice; contingence; psychoanalysis; discourse